Plasticidade fenotípica de três arbóreas tropicais em condições de irradiância contrastantes - Gaburro, Thiele Arpini (2013)
he planting of tropical native tree is rising, and, tothe success of this activity, is needed information about the behavior of the species in relation to the environment in which they operate, like the intensity of radiation. In the forest, the light is a major factor in the establishment and distribution of plant species. Thus, species with extensive plasticity have adaptive advantages in heterogeneous environments. It is believed that the shade tolerant species present, in general, metabolism with low flexibility of response to changes in the environment. On the other hand, light demanding species, acclimate more quickly to changing lighting scheme. In this context, the objective of this study was to assess the phenotypic plasticity of three trees tolerant to shading (Cariniana estrellensis, Cedrela odorataandManilkara salzmannii) in contrasting light conditions considering the physiological, morphological and anatomical. For this, young plants of these species were subjected to two treatments: Full sun and Shadow (5% brightness). After 150 days of experiment, were performed morphological, physiological and anatomical analyses. The three species showed intense changes in the different treatments, providing answers commonly found in species adapted to sun and shade. Shade plants showed a lower R: PA, higher values for AFE, RAF, stem height and higher levels of photosynthetic pigments. Sun plants had higher MFE, soluble carbohydrates, and increased leaf thickness and stomatal density. The plasticity index showed that for the three species, range of physiological responses was greater, followed by morphological and anatomical. The C. odoratashowed higher IP to morphological variables that C. estrellensisand M.Salzmanni,which shows greater phenotypic plasticity of this species from the other. In general, the species studied showed high phenotypic plasticity related to contrasting light, corroborating the hypothesis that shade-tolerant species are able to survive in highly illuminated environment. Due to the ability of acclimatization in full sun, these species are configured as facultative shade species and may be indicated for reforestation programs and restoration of degraded areas